COLLABORATIVE RECOMMENDATIONS USING DEEP LEARNING APPROACHES - B.M.Kishorkumar, K. Nirmaladevi, S.Shanthi V.Jegadeesh, A.Joebastin (International Journal of Advanced Science and Technology, 2020)
The rapid climb of knowledge and communication technology needs the advancement of deep learning in many areas like image processing, speech recognition and linguistic communication processing. Deep learning also gains much attention in the field of recommendations to provide a better detention of user preferences for making effective decisions. Recommendation systems play vital role for suggesting items with various perspective, especially in streaming movie services like Netflix and Hotstar. The proposed deep learning based model helps the user to find new movies to enjoy according their expectations suggested from the similar kind of users. Compared with baseline recommendation models, the proposed deep learning model provides better suggestions to meet the user expectations in a collaborative manner. Proposed model out performs with respect to prediction and loss function.